pH sensor based on chitosan biopolymer / \c Mohd Nasha'ain bin Nordin. - Mohd Nasha'ain Nordin (School of Material Engineering, Universiti Malaysia Perlis, 2010)
The objectives of this research are todesign and fabricate the chitosan pH sensor using electrodeposition techniques; to study the new technique (pH contaminated air exposure) in eliminating the degradation problem; to study the performance and electrical properties of chitosan pH sensor by using the new technique (pH contaminated air exposure); and to characterize microstructure of chitosan thin pH sensors.